Heterotrophic Sulfur Oxidation of Halomonas titanicae SOB56 and Its Habitat Adaptation to the Hydrothermal Environment - Du, Rui; Gao, Di; Wang, Yiting; Liu, Lijun; Cheng, Jingguang; Liu, Jiwen; Zhang, Xiao-Hua; Yu, Min (Frontiers in Microbiology, 2022)
Halomonas bacteria are ubiquitous in global marine environments, however, their sulfur-oxidizing abilities and survival adaptations in hydrothermal environments are not well understood. In this study, we characterized the sulfur oxidation ability and metabolic mechanisms of Halomonas titanicae SOB56, which was isolated from the sediment of the Tangyin hydrothermal field in the Southern Okinawa Trough. Physiological characterizations showed that it is a heterotrophic sulfur-oxidizing bacterium that can oxidize thiosulfate to tetrathionate, with the Na2S2O3 degradation reaching 94.86%. Two potential thiosulfate dehydrogenase related genes, tsdA and tsdB, were identified as encoding key catalytic enzymes, and their expression levels in strain SOB56 were significantly upregulated. Nine of fifteen examined Halomonas genomes possess TsdA- and TsdB- homologous proteins, whose amino acid sequences have two typical Cys-X2-Cys-His heme-binding regions. Moreover, the thiosulfate oxidation process in H. titanicae SOB56 might be regulated by quorum sensing, and autoinducer-2 synthesis protein LuxS was identified in its genome. Regarding the mechanisms underlying adaptation to hydrothermal environment, strain SOB56 was capable of forming biofilms and producing EPS. In addition, genes related to complete flagellum assembly system, various signal transduction histidine kinases, heavy metal transporters, anaerobic respiration, and variable osmotic stress regulation were also identified. Our results shed light on the potential functions of heterotrophic Halomonas bacteria in hydrothermal sulfur cycle and revealed possible adaptations for living at deep-sea hydrothermal fields by H. titanicae SOB56.